2015
DOI: 10.1523/jneurosci.3884-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral Amygdala Response to Food Cues in the Absence of Hunger Is Associated with Weight Gain Susceptibility

Abstract: In rodents, food-predictive cues elicit eating in the absence of hunger (Weingarten, 1983). This behavior is disrupted by the disconnection of amygdala pathways to the lateral hypothalamus (Petrovich et al., 2002). Whether this circuit contributes to long-term weight gain is unknown. Using fMRI in 32 healthy individuals, we demonstrate here that the amygdala response to the taste of a milkshake when sated but not hungry positively predicts weight change. This effect is independent of sex, initial BMI, and tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 78 publications
8
107
3
1
Order By: Relevance
“…Data from longitudinal studies examining the impact of the Taq1A A1 RFLP on weight gain are consistent with the pharmacological data, revealing opposing associations between response to food in DA source or target regions and weight gain as a function of genotype [93, 95, 98] (Figure 1). More specifically, caudate response to anticipated milkshake receipt is negatively associated with weight gain in carriers, but positively associated in non-carriers [93, 95], whereas the opposite is true amygdala response to milkshake in a sated state [98].…”
Section: Taqia Polymorphism (Rs1800497)supporting
confidence: 61%
See 2 more Smart Citations
“…Data from longitudinal studies examining the impact of the Taq1A A1 RFLP on weight gain are consistent with the pharmacological data, revealing opposing associations between response to food in DA source or target regions and weight gain as a function of genotype [93, 95, 98] (Figure 1). More specifically, caudate response to anticipated milkshake receipt is negatively associated with weight gain in carriers, but positively associated in non-carriers [93, 95], whereas the opposite is true amygdala response to milkshake in a sated state [98].…”
Section: Taqia Polymorphism (Rs1800497)supporting
confidence: 61%
“…First, dorsal striatal response to milkshake is associated with measures of impulsivity but not of food reward/reinforcement [97]. Second, a positive association between weight gain and dorsal striatal milkshake response in A1 carriers but not non-carriers was recently reported [98]. Critically, milkshake delivery in this study was unpredicted.…”
Section: Taqia Polymorphism (Rs1800497)mentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, the amygdala responds to food cues (e.g., [32,166]). Additionally, it has been shown that the amygdala's response to food cues are modulated by hunger [47,88,169] and its response in the absence of hunger could predict weight gain susceptibility [159].…”
Section: Amygdala and Cue-induced Feedingmentioning
confidence: 99%
“…(1) While multiple genetic and environmental factors contribute to obesity, (2) modifiable lifestyle factors such as eating behaviors have been subject to considerable research given their relevance to prevention and treatment. (3) Disinhibited eating, characterized by a lack of healthy restraint over eating including eating in the absence of hunger (EAH), (4) may promote excess energy intake, (5) unhealthy weight gain, (68) and obesity. (911) Contrary to pediatric samples, (12) EAH in adults is underexplored, (5, 1317) particularly in the natural environment.…”
Section: Introductionmentioning
confidence: 99%